الآلية الجزيئية للإنضاج المختبري لبييضات الأبقار والظواهر الفيزيولوجية المرافقة لها - سلهب محمد; جبور زهير (Latakia University Journal -Biological Sciences Series, 2016)
يُستخدم الإنضاج المختبري للبييضات بشكل واسع في تقانات التناسل عند الأبقار ويعدّ مرحلة أساسية في إنتاج الأجنة مختبرياً ويخدم عمليات التحسين الوراثي وتشكيل البنوك الوراثية في الحيوانات الزراعية والتي يمكن أن تشكل رصيداً احتياطياً لعشرات السنين. يهدف إنضاج البييضات مختبرياً إلى الحصول على بييضات قابلة للإخصاب وقادرة على دعم مراحل تطور الجنين المبكرة ريثما يتم تفعيل جينوم الجنين، ويصبح مستقلاً، وقادراً على دعم نشاطه ومراحل تطوره المتتابعة. يتجلَى إنضاج البييضة بتغيرات على مستوى النواة والسيتوبلازم وخلايا الركام البيضي (الكومولوس) المحيطة بالبييضة. لاتزال الآلية الجزيئية لهذه التغيرات تشكل محور دراسات وأبحاث كثيرة. هدفت هذه الدراسة البحثية إلى تسليط الضوء على أهم الأبحاث العلمية والدراسات الجينية المعمَقة المرتبطة بالآلية الجزيئية للإنضاج المختبري لبييضات الأبقار وأهم الظواهر الفيزيولوجية المرافقة. In vitro maturation of oocytes is widely used in reproductive technologies in cattle, constituting a crucial step in in-vitro embryos production. It is useful for both genetic improvement and establishment of gene banks that constitute a reserve for many years. In vitro maturation of oocytes permits to obtain fertilizable oocytes that support the early stages of embryo development until embryo genome activation, and the embryo becomes independent and able to support its development. Oocyte maturation is represented by changes at three levels: nucleus, cytoplasm and cumulus cells surrounding the oocyte. The molecular mechanism of these changes is still the focus of many studies and researches. The aim of this review is to show some recent scientific researches on molecular mechanism of oocyte maturation and accompanied physiological changes.